Left Atrial Inexcitability in Children With Congenital Lupus‐Induced Complete Atrioventricular Block - Sylvia Abadir (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2015)
Background Congenital atrioventricular block is a well‐established immunologic complication of maternal systemic lupus erythematosus. We sought to further characterize the electrophysiological manifestations of maternal systemic lupus erythematosus on neonatal atria. Methods and Results Cases of isolated congenital atrioventricular block treated at our center over the past 41 years were identified. Data were extracted from clinical charts, pacemaker interrogations, ECGs, echocardiograms, and histopathological reports, when available. Of 31 patients with isolated congenital atrioventricular block, 18 were negative for maternal antibodies and had normal epicardial atrial sensing and pacing thresholds. In contrast, 12 of 13 patients with positive maternal antibodies had epicardial pacemakers, 5 (42%) of whom had left atrial (LA) inexcitability and/or atrial conduction delay. In 3 patients, the LA could not be captured despite high‐output pacing. The fourth patient had acutely successful LA appendage and left ventricular lead placement. At early follow‐up, an increased delay between the surface P‐wave and intracardiac atrial depolarization was observed, indicative of atrial conduction delay. The fifth patient exhibited LA lead dysfunction, with atrial under‐sensing and an increased capture threshold, 2 weeks after implantation. Biopsies of LA appendages performed in 2 patients showed no evidence of atrial fibrosis or loss of atrial myocytes. Conclusions Herein, we report previously undescribed yet prevalent electrophysiological ramifications of maternal systemic lupus erythematosus, which extend beyond congenital atrioventricular block to encompass alterations in LA conduction, including LA inexcitability. These manifestations can complicate epicardial pacemaker implantation in newborns. In the absence of histological evidence of extensive atrial fibrosis, immune‐mediated functional impairment of electrical activity is suspected.